Endoscopic transcranial transdiaphragmatic approach in a single-stage surgery for giant pituitary adenomas - Wu, Xuechao; Bao, Zhongyuan; Tian, Wei; Wang, Jing; Miao, Zengli; Wang, Qing; Lu, Xiaojie (Frontiers in Oncology, 2023)
Background The treatment for giant pituitary adenomas (GPAs, maximal diameter >4 cm) remains challenging, with remarkable mortality and morbidity, and there is no consensus on the optimal surgical approach. Gross total resection (GTR) for GPAs is difficult to achieve through a single transsphenoidal or transcranial approach. Any residual tumor is at risk for postoperative apoplexy. In this study, we propose a new surgical technique for resecting the GPAs in a sing-stage transcranial surgery. Methods A retrospective review of 4 patients with complicated GPAs, who had been treated via an endoscopic transcranial transdiaphragmatic approach in a single-stage surgery after routine transcranial resection, was performed. The following data was analyzed: clinical characteristics, preoperative imaging studies, resection rate, perioperative morbidity and mortality, as well as postoperative outcomes. Results All patients had nonfunctioning GPAs and preoperative visual disturbances. In three patients, GTR was achieved, and in one patient, near-total resection (90%-100% of the tumor) was achieved. Three patients attained improved postoperative visual function, while one patient’s vision remained unchanged. One patient suffered a deficiency in adrenocorticotropic hormone along with thyroid-stimulating hormone, and one patient developed diabetes insipidus. Notably, none of the patients suffered cerebrospinal fluid leakage. However, one patient developed an epidural hematoma and underwent decompressive craniectomy. Conclusions The endoscopic transcranial transdiaphragmatic approach in a single-stage surgery can be efficiently and safely performed for maximal excision of GPAs with extensive suprasellar extension. Furthermore, relative to the conventional combined or staged approaches, this innovative surgical strategy provides neurosurgeons with a clear operative field with reduced invasiveness.